A pilot study of oxidative pathways in MS fatigue: randomized trial of N‐acetyl cysteine. Issue 4 (6th March 2021) - Krysko, Kristen M.; Bischof, Antje; Nourbakhsh, Bardia; Henry, Roland G.; Revirajan, Nisha; Manguinao, Michael; Nguyen, Khang; Akula, Amit; Li, Yan; Waubant, Emmanuelle
Abstract: Objective: To assess feasibility, tolerability, and safety of N‐acetyl cysteine (NAC) for fatigue in progressive MS. Secondary objectives evaluated changes in fatigue and oxidative pathway biomarkers on NAC versus placebo. Methods: Individuals with progressive MS with Modified Fatigue Impact Scale (MFIS) > t38 were randomized 2:1 to NAC 1250mg TID or placebo for 4 weeks. The primary outcome was tolerability and safety. The secondary outcome to evaluate efficacy was MFIS change from baseline to week 4 between groups. Exploratory biomarker outcomes included change in blood GSH/GSSG ratio (reduced‐to‐oxidized glutathione (GSH)) and in vivo relative GSH using 7T MR spectroscopy (MRS) between groups. Fisher exact test was used for categorical and rank sum for continuous outcomes. Results: Fifiteen were randomized (10 NAC, 5 placebo; mean age 56.1 years, 80% female, median EDSS 6.0). At least one adverse event (AE) occurred in 60% on NAC versus 80% on placebo ( p = 0.75). There were two AEs attributed to NAC in one patient (abdominal pain and constipation), with 94% adherence to NAC. MFIS decreased in both groups at week 4, with the mean improvement of 11‐points on NAC versus 18‐points on placebo ( p = 0.33). GSH/GSSG ratio decreased on placebo (−0.6) and NAC (−0.1) ( p = 0.18). Change in GSH levels to total creatine in anterior and posterior cingulate cortex, insula, caudate, putamen, and thalamus did not differ between groups. Interpretation: NAC was well‐tolerated in progressive MS, although reduction in fatigue on NAC was similar to placebo. Antioxidant blood and MRS biomarkers were not significantly altered by NAC, which could be due to dose, route of administration, time of sample collection, short half‐life, or lack of effect. Registered: clinicaltrials.gov NCT02804594.